THE RANGE EXPANSION OF Parachromis managuensis (GÜNTHER, 1867) (PERCIFORMES, 4 CICHLIDAE) IN JAVA, INDONESIA - Veryl Hasan; Abdul Rahem Faqih; Maftuch Maftuch (SEAMEO BIOTROP, 2022)
The Jaguar cichlid, Parachromis managuensis (Günther, 1867), is native to Central America, with introductions reported from West Java and Central Java Provinces of Indonesia. On 7-8 January 2019, sixteen specimens of P. managuensis were collected from Karangkates, the largest hydropower reservoir in East Java Province of Indonesia. A description of the morphological characters of specimens is provided.